Subspace projection algorithms with robustness to IF errors for GNSS jamming mitigation - Ren, Yuetao; Zhi, Yongfeng; Gao, Huan; Zhang, Jun (Signal, image and video processing, 2023)
Electromagnetic interference broadcasted by low-cost jammers poses a significant threat to global navigation satellite systems (GNSS), severely affecting the reliability of GNSS-enabled systems. Instantaneous frequency (IF)-based subspace projection technique performs excellently in jamming mitigation. However, it is sensitive to estimation errors of the IF of jamming signals. In this paper, we propose two subspace projection algorithms robust to the inaccuracy of IF for single and multiple jamming signals, respectively. First, we construct more subspaces orthogonal to the jamming subspace based on the estimated IF. In the case of inaccurate IF estimates, the interference is projected into the jamming subspace and other constructed subspaces. Then, we propose to improve subspace projection algorithms’ robustness by eliminating more subspaces influenced by jamming signals. The schemes of eliminating subspaces are designed separately for single and multiple jamming signals, respectively. In addition, an IF-based transform with fast calculations is proposed to reduce the computational complexity of the proposed algorithms. Simulation results show that the proposed approaches can suppress the jamming signals effectively in the presence of IF estimate inaccuracy.